Pengaruh Nilai Tukar Mata Uang, Tingkat Suku Bunga Deposito, Dan Tingkat Inflasi Terhadap Pertumbuhan Harga Saham Subsektor Industri Rokok Go Publik Yang Terdaftar Di Bursa Efek Indonesia - Arisyahidin Arisyahidin; Teguh Sukanto (Universitas Islam Kadiri, 2020)
This study aims to know The Influence of Currency Exchange Rates, Deposit Rates, and Inflation Rates on the Stock Price Growth of Go Public Cigarette Industry Subsectors Registered on the Indonesia Stock Exchange. The samples in this study were 4 cigarette companies on the Indonesia Stock Exchange, namely PT. Gudang Garam Tbk, PT. HM. Sampoerna Tbk, PT. Bentoel International Investama Tbk, and PT. Wismilak Inti Makmur Tbk. The data used were stock price growth of the cigarette industry, currency exchange rates, deposit rates and inflation from 2013 to 2016. The analysis technique used was multiple linear regression analysis that tested by F test and t test. Based on the F test results, it was known that currency exchange rates, deposit rates, and inflation rates simultaneously affect the stock prices growth. Based on the results of the t test it was known that the currency exchange rate, and the inflation rate partially affect the stock prices growth, while the deposit interest rate partially didn't affect the stock prices growth